Economic Development; Theory, Policy, and International Relations - Little, Ian Malcolm David (New York Basic Books Inc, 1982)
This book is a comprehensive survey of development economics , including main international economic issues that have given rise to North - South confrontation.
includes notes
includes index and bibliography
ijb 04/02/2019
Loans
Keywords: Economic development; International economic relations; Developing countries